THE ROLE OF LOCAL REVENUE (PAD) REALIZATION IN CENTRAL JAVA’S ECONOMIC GROWTH BETWEEN 2010 AND 2022 - Intan Istikharoh; Didit Purnomo (SEAN Institute, 2023)
Economic growth is increasing per capita output over the long term. By researching the subject of Central Java, several sectors that serve as the main drivers of economic growth and their contributions to regional income can be identified. In this study, a quantitative method is employed to ascertain the influence of local revenue, general allocation funds, special allocation funds, and capital expenditure funds on Central Java's economic growth from 2010 to 2022. The data utilized for this study consists of secondary data in the form of time series data spanning from 2010 to 2022. In this research, the significant variable is the local revenue (PAD) variable. This condition aligns with the hypothesis asserting a positive correlation between economic growth and local revenue. The study uncovers a challenge wherein disparities between theory and real-world observations exist. There are limited academic articles addressing this phenomenon due to its non-universal occurrence, as each region experiences varying influences caused by fluctuations in economic growth rates. Consequently, this study bears substantial influence and utility for academia and society, motivating its undertaking. Reassessing interregional financial equalization for funding needs within the decentralization framework is imperative to achieve equitable objectives. This result can be realized through investments in development, procurement, enhancement, and the upkeep of physical infrastructure. In every district within the province of Central Java, continuous efforts are made to optimize local revenue, leveraging the region's capabilities, thereby fostering heightened economic growth across all districts.